BASIL PERFORMANCE EVALUATION AND WATER QUALITY MONITORING IN A RECIRCULATING AQUAPONICS SYSTEM - Constanța MIHAI; Veronica IVANESCU; Mirela Alina SANDU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Resource scarcity and food security concerns have driven the adoption of innovative farming methods like aquaponics. This sustainable system merges aquaculture and hydroponics, offering a solution to drought and declining soil fertility while efficiently producing both fish and vegetables. The global aquaponics market is projected to more than double by 2028 due to its economic and environmental advantages. This study investigated basil (Ocimum basilicum) growth performance and water quality dynamics in a recirculating aquaponic system stocked with common carp (Cyprinus carpio). The system demonstrated effective nutrient cycling with stable water quality parameters conducive to plant health. Over four weeks, basil exhibited vigorous growth with significant increases in stem length, leaf size, and leaf number. These results highlight aquaponics' potential for efficient resource use and sustainable production of fish and high-value crops. The study provides valuable insights into optimizing aquaponic systems for improved food security and environmental sustainability.